Mining for characterising patterns in literature using correspondence analysis: an experiment on French novels. - Frontini, Francesca; Boukhaled, Mohamed Amine; Ganascia, Jean-Gabriel (DHQ: Digital Humanities Quarterly, 2017)
This paper presents and describes a bottom-up methodology for the detection of stylistic traits in the syntax of literary texts. The extraction of syntactic patterns is performed blindly by a sequential pattern mining algorithm, while the identification of significant and interesting features is performed at a later stage by using correspondence analysis and by ranking patterns by contribution.